The Impact of Camtasia-Based Learning Videos on Vocabulary Mastery in Eighth-Grade MTsN 1 Padang Pariaman: Pengaruh Video Pembelajaran Berbasis Camtasia terhadap Penguasaan Mufradat di Kelas VIII MTsN 1 Padang Pariaman - Yulva Maya Padilah; Amin Harahap; Haerani Kadar; Raudhatunnur (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2024)
Purpose – This research aims to determine the impact of Camtasia-based learning videos on vocabulary mastery among eighth-grade students at MTsN 1 Padang Pariaman Design/methods/approach – This research uses a quantitative approach with a quasi-experimental design and a Non-Equivalent Control Group Design. The population consisted of 168 eighth-grade students from MTsN 1 Padang Pariaman, with a sample of 56 students selected non-randomly. Class VIII.6 (28 students) was the experimental group, while Class VIII.5 (28 students) was the control group. Data were collected through pre-tests, post-tests, observations, and documentation. Analysis included descriptive statistics, normality testing (Shapiro-Wilk), and homogeneity testing (Levene’s test). A paired-sample t-test in SPSS version 29 was used to assess the significance of vocabulary mastery differences. Findings – Findings show significant improvement in the experimental group's vocabulary mastery, with pre-test scores averaging 60.178 and post-test scores increasing to 83.035. The t-test analysis revealed a calculated